2022
DOI: 10.3390/cancers14040981
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis in Mesothelioma: Potential Role of Lysyl Oxidases

Abstract: Immunotherapies (such as checkpoint inhibitors) and standard chemotherapies (such as cisplatin) have limitations in the successful treatment of malignant pleural mesothelioma (MPM). Fibrosis is the accumulation of collagen in the extracellular matrix (ECM) of tissues, making them denser than that of healthy tissues and thereby affecting drug delivery and immune cell infiltration. Moreover, fibrosis severely affects the patient’s breathing and quality of life. The production of collagen and its assembly is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 185 publications
(182 reference statements)
0
4
0
Order By: Relevance
“…Given the clinical similarities of fibrosis that characterizes both MESO 37 and PDAC, we hypothesized that there may also be similar pathology findings that explain the relevance of DeCAF subtypes in MESO. We found that DeCAF subtypes were associated with histological type (p = 0.001) with 93% (53/57) of epithelioid type tumors having a restCAF subtype (Fig.5d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Given the clinical similarities of fibrosis that characterizes both MESO 37 and PDAC, we hypothesized that there may also be similar pathology findings that explain the relevance of DeCAF subtypes in MESO. We found that DeCAF subtypes were associated with histological type (p = 0.001) with 93% (53/57) of epithelioid type tumors having a restCAF subtype (Fig.5d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in some tumors the cross-linking of collagen and elastin fibers mediated by LOX is increased. In particular, LOX expression is upregulated in many tumors, for example mesothelioma, downstream of hypoxia (HIFs) by a mechanism that is, in part, driven by TGFβ ( 22 , 85 , 86 ). An unbalanced increase in LOX expression and activity promotes an increase in ECM stiffness that induces mechanical activation of latent TGFβ and fuels the initiation of a vicious cycle that maintains an inflammatory environment and promotes tumor progression ( 83 ).…”
Section: Inflammation In Desmoplastic Matrix Remodelingmentioning
confidence: 99%
“…This implies that inhibitors of lysyl oxidases may turn out to be useful therapeutic agents for the treatment of many types of cancer. In addition, inhibition of lysyl oxidases may assist in the control of fibrotic diseases, such as idiopathic lung fibrosis and liver cirrhosis, and may help to reduce tumor desmoplasia [ 118 , 119 , 120 ]. The first attempt in this direction was the development of a LOXL2-targeting antibody that showed promise in pre-clinical studies [ 43 , 121 , 122 ].…”
Section: Development Of Anti-tumorigenic Therapeutics Targeting Lysyl...mentioning
confidence: 99%